2004
DOI: 10.1111/j.1365-2958.2003.03968.x
|View full text |Cite
|
Sign up to set email alerts
|

GW domains of the Listeria monocytogenes invasion protein InlB are required for potentiation of Met activation

Abstract: SummaryThe Listeria monocytogenes protein InlB promotes intracellular invasion by activating the receptor tyrosine kinase Met. Earlier studies have indicated that the LRR fragment of InlB is sufficient for Met activation, but we show that this is not the case unless the LRR fragment is artificially dimerized through a disulphide bond. In contrast, activation of Met proceeds through monomers of intact InlB and, at physiologically relevant concentrations, requires coordinated action in cis of both InlB N-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 49 publications
6
96
0
Order By: Relevance
“…Purified InlB was shown to bind to purified GAGs through its GW domains and invasion of Chinese hamster ovary (CHO) cells is potentiated 10-fold when GAGs are produced at the cell surface ). These results suggest that the GW modules of InlB present the dual function of attaching InlB to the bacterial cell wall and of enhancing L. monocytogenes entry triggered by the LRRs domain, reinforcing the similarities between the mechanisms of cell activation exerted by InlB and HGF Banerjee et al 2004). The GW domains of InlB have been reported to bind another ubiquitous cellular molecule, the receptor of the globular part of the complement component C1q (gC1q-R) Marino et al 2002).…”
Section: Inlb Interacts With the Hepatocyte Growth Factor Receptor Mementioning
confidence: 78%
See 1 more Smart Citation
“…Purified InlB was shown to bind to purified GAGs through its GW domains and invasion of Chinese hamster ovary (CHO) cells is potentiated 10-fold when GAGs are produced at the cell surface ). These results suggest that the GW modules of InlB present the dual function of attaching InlB to the bacterial cell wall and of enhancing L. monocytogenes entry triggered by the LRRs domain, reinforcing the similarities between the mechanisms of cell activation exerted by InlB and HGF Banerjee et al 2004). The GW domains of InlB have been reported to bind another ubiquitous cellular molecule, the receptor of the globular part of the complement component C1q (gC1q-R) Marino et al 2002).…”
Section: Inlb Interacts With the Hepatocyte Growth Factor Receptor Mementioning
confidence: 78%
“…Intriguingly, gC1q-R is a glycosylphosphatidylinositol (GPI)-anchored protein that does not present a cytoplasmic domain, suggesting that signaling on interaction with InlB is transduced through another cofactor. It has been reported that interaction between gC1q-R and InlB GW domains antagonizes rather than enhances InlB signaling (Marino et al 2002;Banerjee et al 2004). Therefore, the precise role of gC1q-R in L. monocytogenes infection remains to be clarified.…”
Section: Inlb Interacts With the Hepatocyte Growth Factor Receptor Mementioning
confidence: 99%
“…109 GAG receptors facilitate the detachment of InlB from the bacterial surface and InlB clustering at the host cell surface, thus promoting strong Met activation and bacterial entry. 81,82 Although InlB has several receptors, it is well accepted that Met is the major InlB signaling receptor. InlB has the ability to induce Met autophosphorylation and the recruitment of adaptor proteins, such as Cbl, Shc and Gab1, [83][84][85] that lead to the activation of PI3-kinase 86 and small GTPase Rac1.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…11 InlB 321 , additionally containing the so-called inter-repeat (IR) region is the smallest InlB fragment that promotes Met phosphorylation as a soluble, monomeric protein. 10 The IR region is followed by a poorly characterized B-repeat and three C-terminal, highly basic GW domains that do not bind Met on their own, 10 but significantly enhance Met phosphorylation and are required for a full cellular response. 10; 12 The synergistic effect of the N-and C-terminal InlB domains depends on the presence of heparan sulfate proteoglycans (HSPGs) on the host cell surface 10; 12 and the GW domains strongly interact with negatively charged heparin in vitro, resulting in clustering of InlB.…”
Section: Introductionmentioning
confidence: 99%
“…9 The function of individual domains for binding and activation of Met has been characterized in depth. A fragment consisting only of the N-terminal Cap region and the leucine-rich repeat (LRR) region is sufficient for high affinity binding of Met 6 and can induce Met activation when it is artificially dimerized by a disulfide-bridge 10 or clustered by immobilization on latex beads. 11 InlB 321 , additionally containing the so-called inter-repeat (IR) region is the smallest InlB fragment that promotes Met phosphorylation as a soluble, monomeric protein.…”
Section: Introductionmentioning
confidence: 99%